Kinetic changes in serum KL-6 levels predict disease progression in patients with systemic sclerosis-associated interstitial lung disease. (January 2022) - Watanabe, Satoshi; Kase, Kazumasa; Saeki, Keigo; Ohkura, Noriyuki; Murata, Akari; Waseda, Yuko; Takato, Hazuki; Ichikawa, Yukari; Yasui, Masahide; Kasahara, Kazuo
Abstract: Background: The clinical course of patients with systemic sclerosis-associated interstitial lung disease (SSc-ILD) is highly variable. The Krebs von den Lungen-6 (KL-6) glycoprotein is a promising biomarker for reflecting epithelial injury. However, serum KL-6 and its association with the progression of SSc-ILD have been understudied. Methods: We reviewed 77 consecutive patients with SSc-ILD seen from 2004 to 2016. A longitudinal study of forced vital capacity (FVC), serum KL-6 levels, and changes in KL-6 levels from baseline (ΔKL-6) was conducted. The progression of ILD was defined as ≥10% relative decline in FVC predicted or 5%–10% decline in FVC predicted along with radiological progression on chest computed tomography. The risk factors for ILD progression were assessed by univariate and multivariate regression. Results: During a 5-year follow-up period, 10 (13%) patients showed rapid progression of ILD within 2 years, 39 (51%) showed overall progression during the 5 years, and 28 (36%) had stable disease. Most patients with progressive ILD showed elevations in serum KL-6 levels over the initial 1-year follow-up period. The best cut-off value for ΔKL-6 that predicted progression of ILD was 193 U/mL (sensitivity 81.6%, specificity 92.9%). Multivariate analysis adjusted by age, sex, smoking status, and immunosuppressant use found that diffuse cutaneous SSc (hazard ratio [HR] 4.51; 95% confidence interval [CI] 1.56–13.04) and ΔKL-6 > 193 U/mL from baseline (HR 7.19; 95% CI 3.30–15.69) were independent predictors for progression of SSc-ILD. Conclusion: Changes in the KL-6 level can be useful for predicting disease progression in patients with SSc-ILD. Highlights: KL-6 is a promising biomarker for reflecting epithelial injury in SSc-ILD. Disease progression and elevated KL-6 levels occur simultaneously in SSc-ILD. Kinetic changes in KL-6 levels are useful for predicting SSc-ILD progression.